2007
DOI: 10.1364/oe.15.006569
|View full text |Cite
|
Sign up to set email alerts
|

Efficient coupling into slow-light photonic crystal channel guides using photonic crystal tapers

Abstract: Photonic crystal tapers have been designed for coupling of light from ridge waveguides into low group velocity photonic crystal channel guides. The coupling efficiency is increased from 3 % (case of butt-coupling) to 97 % for frequencies in the band-edge region, corresponding to a group index close to 100, as predicted using 2D finite-difference time-domain simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 17 publications
(21 reference statements)
0
36
0
Order By: Relevance
“…9,10 Yet, the main attraction was directed toward the utilization of the tapered PCWs that facilitate adiabatic mode conversion. [11][12][13][14][15][16][17][18][19][20] The supporting theoretical studies show promise for considerably high coupling efficiencies when we make use of these tapered PCWs. 21,22 Nonetheless, tapered PCWs have simultaneously led to serious drawbacks.…”
Section: Introductionmentioning
confidence: 73%
“…9,10 Yet, the main attraction was directed toward the utilization of the tapered PCWs that facilitate adiabatic mode conversion. [11][12][13][14][15][16][17][18][19][20] The supporting theoretical studies show promise for considerably high coupling efficiencies when we make use of these tapered PCWs. 21,22 Nonetheless, tapered PCWs have simultaneously led to serious drawbacks.…”
Section: Introductionmentioning
confidence: 73%
“…Compared to the case with undoped silicon, the electric field across the slot can be increased, thus enabling better RF interaction within the EO polymer infiltrated in the slot. To effectively couple light into the slow light region, a PCW taper from W1.08 to W1.0 (the air hole spacing outside the slot is changed from dW=1.08√3a to dW=√3a) is designed to minimize the group index mismatch between the strip waveguide and the slot PCW [65,66], as shown in Fig. 6 (a).…”
Section: Silicon/polymer Hybrid Photonic Crystal Waveguide Modulmentioning
confidence: 99%
“…This hybrid nanophotonic modulator is fabricated on a SOI wafer with 230nm slightly doped top silicon and 3µm buried oxide. Details of fabrication are described in [65]. The device is fabricated by using electron-beam lithography and RIE in a single patterning/etch step, whereas the gold electrodes are patterned by photolithography and lift-off processes [ Fig.…”
Section: Silicon/polymer Hybrid Photonic Crystal Waveguide Modulmentioning
confidence: 99%
“…Different research groups investigated the coupling problem and found novel solutions. [4][5][6][7][8][9][10][11] Tapered couplers, 4,5 adiabatic coupling configurations, 6 tapered PC modes, [7][8][9] and graded index PCs (Refs. 10 and 11) were proposed.…”
Section: Introductionmentioning
confidence: 99%